2023
DOI: 10.3847/1538-4357/acd2d3
|View full text |Cite
|
Sign up to set email alerts
|

A Census of WISE-selected Dual and Offset AGNs Across the Sky: New Constraints on Merger-driven Triggering of Obscured AGNs

Abstract: Pairs of galaxies hosting active galactic nuclei (AGNs) are powerful probes of merger-driven supermassive black hole (SMBH) growth as they can resolve individual AGNs and trace mergers over a large range of physical separations. To exploit this on a large scale for the first time for both obscured and unobscured AGNs, we use the photometric redshifts of AGNs selected by the Wide-field Infrared Survey Explorer (WISE) to find probabilistic pairs (<100 kpc separations) across the sky, along with a comparison s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 118 publications
1
5
0
Order By: Relevance
“…Our results are consistent with simulations and phenomenological models that found no significant differences in the Eddington ratios of AGNs in galaxy mergers (Steinborn et al 2016;Weigel et al 2018;McAlpine et al 2020). In addition, observations of WISE AGNs in galaxy pairs also reported no significant correlation of the AGN merger fraction with L bol /M * ( Barrows et al 2023). A further study of broad-line AGNs at z ∼ 2 also found that major mergers do not correlate highaccretion AGNs (Marian et al 2019).…”
Section: Galaxy Mergers Do Not Trigger Higher Smbh Accretion Ratesmentioning
confidence: 96%
See 1 more Smart Citation
“…Our results are consistent with simulations and phenomenological models that found no significant differences in the Eddington ratios of AGNs in galaxy mergers (Steinborn et al 2016;Weigel et al 2018;McAlpine et al 2020). In addition, observations of WISE AGNs in galaxy pairs also reported no significant correlation of the AGN merger fraction with L bol /M * ( Barrows et al 2023). A further study of broad-line AGNs at z ∼ 2 also found that major mergers do not correlate highaccretion AGNs (Marian et al 2019).…”
Section: Galaxy Mergers Do Not Trigger Higher Smbh Accretion Ratesmentioning
confidence: 96%
“…The discrepancies between these MaNGA studies may be due to differing volume corrections and aperture sizes (e.g., Steffen et al 2023). Studies of X-ray-and mid-infrared-selected AGNs in galaxy also found that the fraction of AGNs increases as the pair separation decreases (e.g., Koss et al 2012;Barrows et al 2017;Stemo et al 2021;Barrows et al 2023), though these studies did not search for a galaxy mass dependence.…”
Section: An Excess Of Agns In Post-coalescence Galaxy Mergers Of Stel...mentioning
confidence: 97%
“…Assuming these offsets are due to enhanced luminosities, satellite accretion events may have a significant impact on IMBH growth. If these events are common, they may represent a nonnegligible mechanism in the buildup of black hole mass in the Universe (e.g., Barrows et al 2023). However, no evidence is seen for the mass-normalized HLX luminosities to evolve with ΔS, suggesting that these enhanced L X to M å ratios are not strongly dependent on the stage of orbital evolution probed by our sample (though such a correlation may be washed out by random variations in projection angle and orbital trajectory).…”
Section: The Role Of Galaxy Mergers For Imbh Growthmentioning
confidence: 99%
“…Because of the increase of nuclear star formation and nuclear activity in mergers (e.g., Satyapal et al 2014), it is reasonable to consider that the incidence and properties of outflows may depend on the morphology and/or environment of the galaxy. However, major mergers alone are not sufficient to account for the entire AGN population (Draper & Ballantyne 2012), as they appear to be associated mainly with ultraluminous infrared galaxies (ULIRGs; Treister et al 2012;Glikman et al 2015;Barrows et al 2017Barrows et al , 2023. That is, only the most luminous AGN phases are associated with major mergers, while less luminous AGNs appear to be driven by secular processes (Treister et al 2012).…”
Section: Introductionmentioning
confidence: 99%